Le génitif anglais et la métaphore adamczewskienne de soudure - Evelyne Chabert (Anglophonia)
As is common in cases of information packaging, in which a speaker chooses the form best matching their intention, various models have been exposed in the linguistic literature to account for the factors at play in the choice between the genitive construction (the dog’s kennel) and the of-phrase (the kennel of the dog). One widely accepted model in France is Henri Adamczewski’s, according to which the distinction is motivated by the speaker’s representation of the relation between the possessor and the possessee. In this view, a speaker is likely to select the genitive construction if their aim is to signal that, to them, the possessor-possessee relation is - metaphorically - “fused”, i.e. firmly established in their mind prior to the enunciation, whereas, negatively, selection of OF (which is to be related to its etymological ancestor, OFF), is meant to signal that the two referents brought together are not intrinsically linked, not inherently associated. The aim of this article is to discuss Adamczewski’s account of the possessive constructions starting from the examples he uses in Grammaire linguistique de l’anglais (1998). A close examination shows that they are questionable as illustrations of his theory. Besides, counter-examples can be found to invalidate the “fusion” model.